A Study on Contribution of Women in the Development of Rural Tourism, with Special Reference Selected Rural Tourism Destinations of Malnad Region of Karnataka State - K, Vikrama. D. (International Journal of Membrane Science and Technology, 2023)
Rural tourism in India is one of the emerging sectors. Rural tourism is one of the major alternative sources of income for rural population. Rural people can use available resources more effectively and efficiently. Contributions of rural women in tourism activities are neglected or not recognized. This paper tries to highlight the problems and prospects of rural women involvement development of rural tourism in Malnad region of Karnataka state.